OPTIMALISASI PENDIDIKAN AGAMA ISLAM MELALUI PELATIHAN PEMULASARAAN JENAZAH DI SMA MUHAMMADIYAH 25 PAMULANG - Ma’muroh, Ma’muroh; Rohanah, Rohanah; Dora, Rafika; Yulia, Yulia; Dewi, Liza Puspa (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2025)
ABSTRACT Islamic Religious Education (PAI) plays a crucial role in shaping students' character and spirituality, while also equipping them with practical skills that are valuable in community life. Among these essential skills, the proper handling of deceased persons (jenazah care)—a collective obligation (fardhu kifayah) in Islam—is rarely taught in depth at schools. Beyond imparting religious knowledge, this skill also fosters students’ sense of social responsibility within the Muslim community. This community service program aims to enhance the understanding and practical skills of students at SMA Muhammadiyah 25 Pamulang in performing jenazah care through a training initiative based on Participatory Action Research (PAR). The PAR approach enables students to engage actively in experiential learning, wherein they not only study the theoretical aspects but also practice each stage of jenazah care, including washing, shrouding, and burial in accordance with Islamic law. The training outcomes indicate a significant improvement in students’ competencies and comprehension, as well as an increased awareness of their social responsibilities as members of the Muslim ummah. In addition to enriching the quality of Islamic Religious Education, this program serves as a model of applied and participatory education, which is expected to be sustainably integrated into the school curriculum. By providing hands-on experiences and a deeper understanding of religious obligations, the training equips students with essential life skills and prepares them to contribute meaningfully to society, in line with core Islamic values. Furthermore, this program demonstrates the potential of PAR-based approaches to develop impactful and sustainable models of religious education in schools. ABSTRAK Pendidikan Agama Islam (PAI) memiliki peran penting dalam membentuk karakter dan spiritualitas siswa, serta membekali mereka dengan keterampilan praktis yang bermanfaat dalam kehidupan bermasyarakat. Di antara keterampilan penting tersebut, pemulasaraan jenazah—kewajiban kolektif (fardhu kifayah) dalam Islam—jarang diajarkan secara mendalam di sekolah. Selain memberikan pengetahuan agama, keterampilan ini juga memperkuat rasa tanggung jawab sosial siswa dalam komunitas Muslim. Program pengabdian ini bertujuan untuk meningkatkan pemahaman dan keterampilan siswa SMA Muhammadiyah 25 Pamulang dalam melaksanakan pemulasaraan jenazah melalui pelatihan berbasis Participatory Action Research (PAR). Pendekatan PAR memungkinkan siswa terlibat aktif dalam pembelajaran praktis, di mana mereka tidak hanya mempelajari teori, tetapi juga mempraktikkan setiap tahapan pemulasaraan jenazah, mulai dari memandikan, mengkafani, hingga menguburkan sesuai dengan syariat Islam. Hasil pelatihan menunjukkan peningkatan signifikan dalam keterampilan dan pemahaman siswa, serta peningkatan kesadaran mereka akan tanggung jawab sosial sebagai anggota komunitas Muslim. Selain meningkatkan kualitas pembelajaran PAI, program ini berfungsi sebagai model pendidikan yang aplikatif dan partisipatif, yang diharapkan dapat diintegrasikan secara berkelanjutan dalam kurikulum sekolah. Dengan memberikan pengalaman langsung dan pemahaman tentang kewajiban agama, pelatihan ini membekali siswa dengan keterampilan hidup yang berharga dan mempersiapkan mereka untuk berkontribusi aktif dalam masyarakat, sesuai dengan nilai-nilai inti Islam. Program ini juga menunjukkan potensi pendekatan berbasis PAR dalam menciptakan model pendidikan agama yang berkelanjutan dan berdampak di sekolah-sekolah.